Preparation and application of a composite catalyst
The barium titanate/manganese dioxide composite material with shell and core structure was prepared by atomic layer deposition method, which solved the problem of unstable interface coupling, significantly improved the catalytic degradation efficiency, and achieved efficient removal of organic pollutants during the processing and extraction of rare earth elements. degradation.
Patent Information
- Application Number
- CN202410017452.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-05
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-01-05
AI Technical Summary
The prior art is difficult to accurately modify the coupling interface between manganese dioxide and barium titanate at the atomic level, resulting in poor catalytic performance of composite materials.
Using the atomic layer deposition method, barium titanate, bis(cyclopentadiene)manganese and O3 are used as raw materials, and reaction deposition is performed in anhydrous ethanol solvent to form a barium titanate/manganese dioxide composite material with a shell and core structure. By adjusting the number of cycles of reaction deposition and adjusting the thickness of manganese dioxide, the catalytic performance can be improved.
The uniform and stable deposition of manganese dioxide on the surface of barium titanate is achieved to form a complete core-shell structure, which significantly improves the catalytic degradation efficiency of the composite material and has an efficient catalytic degradation effect on organic pollutants generated during the processing and extraction of rare earth elements.
Smart Images

Figure CN117839684B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalysis, and in particular to a preparation method of a composite catalyst and application thereof. Background Art
[0002] Rare earth elements have become an indispensable core element in the latest cutting-edge high-tech application fields. A large amount of organic solvents and surfactants are used in the extraction and processing of rare earths. These organic substances will be carried away by wastewater. If not handled properly, they will cause serious pollution of water sources and soil, and damage the ecosystem.
[0003] Barium titanate is a beneficial piezoelectric material. It has been studied as a piezoelectric catalyst because of its significant catalytic ability in pollutant degradation. Manganese dioxide nanomaterials can improve the utilization rate of visible light irradiation due to their narrow band gap, large surface area and negative surface charge. Combining barium titanate with manganese dioxide to construct a nanocomposite material can maximize the use of nanoscale surface area to accelerate electron transfer. At the same time, the piezoelectric effect of the piezoelectric material itself can promote the generation of highly active groups, significantly enhance the photocatalytic degradation effect, and effectively degrade some organic pollutants, thereby achieving the purpose of protecting the ecological environment.
[0004] To date, a variety of methods have been explored to synthesize barium titanate-manganese dioxide nanocomposites, including electrospinning, hydrothermal method, solvothermal reaction, and coprecipitation. However, these traditional preparation methods often lead to component agglomeration, substrate deformation, or are limited by cumbersome and complex processes. In addition, traditional preparation methods make it difficult to precisely modify the coupling interface between manganese dioxide and barium titanate at the atomic level. That is, the following issues need to be considered and resolved when constructing composite materials using barium titanate and manganese dioxide: (1) being able to controllably and orderly deposit manganese dioxide on barium titanate to form a core-shell structure so that the composite material exhibits excellent synergistic properties; (2) understanding the reaction mechanism of the material interface and the catalytic degradation of the target material to enhance the photocatalytic efficiency. Therefore, preparing barium titanate-manganese dioxide nanocomposites through a precise and effective synthesis method so that the composite material has a higher catalytic degradation efficiency has always been the focus of research. Summary of the invention
[0005] The present invention aims to provide a method for preparing a composite catalyst, which is specifically a barium titanate / manganese dioxide composite material.
[0006] Another object of the present invention is to use the composite catalyst prepared by the above method to effectively catalyze and degrade organic pollutants generated during the extraction and processing of rare earths, thereby improving the protection of the ecosystem.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A preparation method of a composite catalyst is characterized in that: barium titanate, bis(cyclopentadienyl)manganese and O3 are used as raw materials, anhydrous ethanol is used as solvent, and an atomic layer deposition method is used for preparation. Specifically, barium titanate and anhydrous ethanol are mixed and ultrasonically prepared into a suspension, bis(cyclopentadienyl)manganese is used as a manganese source, and reaction deposition is carried out in an O3 atmosphere, and then a mixed gas of H2 and Ar is introduced for treatment to obtain a barium titanate / manganese dioxide composite material with a core-shell structure.
[0009] Furthermore, the dosage ratio of barium titanate to anhydrous ethanol in the suspension is 1 g:4-6 mL, and the volume ratio of the suspension to bis(cyclopentadienyl)manganese is 1:2.
[0010] Furthermore, the bis(cyclopentadienyl)manganese is brought into the reaction chamber by N2 with a gas flow rate of 5-8 sccm.
[0011] Furthermore, the temperature of the reaction deposition is 250-280° C., the gas flow rate of O3 is 4-6 mL / min, the gas flow rate of the mixed gas of H2 and Ar is 4-6 mL / min, and the volume ratio of H2 to Ar is 9:1-9.5:0.5.
[0012] Furthermore, the parameters of one cycle (one circle) in the reaction deposition are: a manganese source pulse of 2s, a N2 purge of 10s, an O3 reaction pulse of 2s, a mixed gas pulse of H2 and Ar of 1s, a nitrogen purge of 15s, 50 to 80 cycles of cyclic reaction deposition, and 50 to 80 cycles of cyclic reaction deposition.
[0013] The atomic layer deposition method can deposit the sediment layer by layer on the substrate surface in the form of a thin film at the nanoscale, so that the deposited particles have good uniformity and conformality. However, during the preparation process, when barium titanate was used as the substrate and manganese dioxide was deposited on its surface by reaction, it was found that the deposition effect of manganese dioxide on the surface of barium titanate was not ideal. The binding stability of manganese dioxide on the surface of barium titanate was poor, and some of it fell off, resulting in poor catalytic performance of the composite material.
[0014] In the present invention, di(cyclopentadienyl)manganese is used as a manganese source and O3 is used as an oxidant. After reaction and deposition, a small amount of H2 is introduced for treatment. Manganese dioxide is deposited evenly on the surface of barium titanate, forming a complete core-shell composite material with barium titanate as a core and manganese dioxide as a shell. The generated manganese dioxide is evenly and stably deposited on the surface of barium titanate, with excellent bonding strength and no partial shedding. Compared with single manganese dioxide and barium titanate, the band gap of the composite material is significantly reduced, thereby improving the catalytic performance of the material.
[0015] By regulating the number of reaction deposition cycles, the thickness of manganese dioxide grown by reaction deposition on the surface of barium titanate is adjusted, so that it has better catalytic degradation efficiency within a specific range.
[0016] Most specifically, a method for preparing a composite catalyst is characterized by being carried out according to the following steps:
[0017] (1) Add barium titanate to anhydrous ethanol and ultrasonicate for 1 min to obtain a suspension. The suspension is coated on a quartz glass sheet and placed in the reaction chamber of an atomic layer reaction device. The chamber is evacuated to 1×10 -5 Pa vacuum state, the amount ratio of barium titanate and anhydrous ethanol in the suspension is 1g:4~6mL;
[0018] (2) N2 was used as a carrier gas to bring the manganese source di(cyclopentadienyl)manganese into the reaction chamber with a carrier gas flow rate of 5-8 sccm. The reaction chamber temperature was 250-280°C and the reaction deposition was carried out in an O3 atmosphere. Then, a mixed gas of H2 and Ar was introduced for treatment. In one reaction cycle (one deposition cycle), the manganese source pulse was 2 s, the N2 purge was 10 s, the O3 reaction pulse was 2 s, the H2 and Ar mixed gas pulse was 1 s, and the nitrogen purge was 15 s. The cyclic reaction deposition was performed for 50-80 cycles to obtain a core-shell structured barium titanate-manganese dioxide composite material. The volume ratio of the suspension to di(cyclopentadienyl)manganese was 1:2.
[0019] The barium titanate-manganese dioxide composite catalyst prepared by the above method is used in the degradation of organic matter in wastewater, especially in the catalytic degradation of organic pollutants produced during the processing and extraction of rare earth elements, and has a good degradation effect on pollutants in wastewater.
[0020] Preferably, the barium titanate-manganese dioxide composite catalyst is used for the degradation of bisphenol A, toluene, benzene and chloroform in wastewater.
[0021] The present invention has the following technical effects:
[0022] The present invention solves the problem of poor stability of atomic layer deposited manganese dioxide on the surface of barium titanate. Stable and uniform manganese dioxide is prepared by atomic layer deposition on the surface of barium titanate, forming a composite material with a completely wrapped core-shell structure, and by adjusting the thickness of the manganese dioxide on the surface of barium titanate, the photocatalytic performance of the composite material is effectively improved, and efficient catalytic degradation is formed for organic pollutants generated by a large amount of organic solvents and surfactants used in the process of rare earth element processing and extraction. It has an excellent photocatalytic degradation effect on bisphenol A and similar pollutants such as halogenated hydrocarbons, aromatic hydrocarbons and their derivatives, and the degradation rate reaches more than 90%. Under the condition that rare earth elements have become an indispensable core element in the latest cutting-edge high-tech application fields, the pollution and damage to the environment in the process of rare earth processing and extraction is effectively reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 : Transmission electron microscopy images of barium titanate / manganese dioxide composites prepared with different reaction deposition cycles.
[0024] Figure 2 : Degradation efficiency curve of bisphenol A of barium titanate / manganese dioxide composite materials prepared with different reaction deposition cycles. DETAILED DESCRIPTION
[0025] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above-mentioned contents of the present invention.
[0026] Example 1
[0027] A method for preparing a composite catalyst is carried out according to the following steps:
[0028] (1) Add barium titanate to anhydrous ethanol and ultrasonicate for 1 min to obtain a suspension. The suspension is coated on a quartz glass sheet and placed in the reaction chamber of an atomic layer reaction device. The chamber is evacuated to 1×10 -5 Pa vacuum state, the amount ratio of barium titanate and anhydrous ethanol in the suspension is 1g:4~6mL;
[0029] (2) N2 was used as a carrier gas to bring the manganese source di(cyclopentadienyl)manganese into the reaction chamber with a carrier gas flow rate of 5 sccm. The reaction deposition was carried out under the conditions of a reaction chamber temperature of 260 °C and a volume ratio of O3 and H2 / Ar of 9.5:0.5. In one reaction cycle, the manganese source pulse was 2 s, the N2 purge was 10 s, the O3 reaction pulse was 2 s, the H2 and Ar mixed gas pulse was 1 s, and the nitrogen purge was 15 s. The cyclic reaction deposition was repeated for 60 cycles (60 deposition circles) to obtain a core-shell structured barium titanate-manganese dioxide composite material with a volume ratio of suspension to di(cyclopentadienyl)manganese of 1:2.
[0030] During the reaction deposition process, the barium titanate / manganese dioxide composite materials with different deposition cycles were prepared by adjusting the deposition cycles (cycles) according to the preparation method of Example 1. Figure 1 Are the corresponding transmission electron microscope images, where a, b and c correspond to the barium titanate / manganese dioxide composite materials prepared with 20, 60 and 150 deposition cycles, respectively. It can be seen that with the increase in the number of deposition cycles, the thickness of MnO2 coated on the surface of BaTiO3 in the composite material also gradually increases.
[0031] Degradation effect of barium titanate / manganese dioxide composite materials on organic matter:
[0032] First, 50 mL of 10 mg / L bisphenol A solution was placed in a 100 mL glass reaction container, and then 20 mg of barium titanate / manganese dioxide composite material was added. The mixture was magnetically stirred in a light-proof and air-filled environment for 60 minutes. The purpose of stirring with air was to allow the surface of the composite material to reach an adsorption / desorption equilibrium with the bisphenol A solution. Then, the UV lamp was turned on with a power of 200 W. The lamp was placed about 5 cm above the beaker to irradiate the bisphenol A solution containing the barium titanate / manganese dioxide composite material. At the same time, an ultrasonic oscillator was used to ultrasonically vibrate the solution. The solution in the beaker was extracted every 10 minutes, and the absorbance of the supernatant was extracted and analyzed. The degradation rate of bisphenol A by the barium titanate / manganese dioxide composite material obtained by detection was as follows: Figure 2 As shown. It can be seen that the degradation rate of bisphenol A by single barium titanate, single manganese dioxide, and barium titanate / manganese dioxide composite materials prepared by different deposition cycles is significantly different, among which the barium titanate / manganese dioxide composite material prepared by 60 cycles of reaction deposition has the best degradation effect on bisphenol A, while the degradation effect of bisphenol A by barium titanate / manganese dioxide composite materials with lower or higher deposition cycles has decreased to varying degrees. The degradation efficiency of bisphenol A by the barium titanate / manganese dioxide composite material prepared in Example 1 reaches 93%.
[0033] Comparative Example 1
[0034] The difference from Example 1 is that the manganese source di(cyclopentadienyl)manganese used in Example 1 is replaced with Mn(thd)3 (tri(2,2,6,6-tetramethyl-3,5-heptanedione)manganese), and the remaining steps are consistent with Example 1 to prepare a barium titanate / manganese dioxide composite material.
[0035] In the same manner, the barium titanate / manganese dioxide composite material prepared in Comparative Example 1 was used to catalyze the degradation of bisphenol A. Its degradation efficiency was significantly lower than that of the barium titanate / manganese dioxide composite material prepared in Example 1.
[0036] Since the barium titanate / manganese dioxide composite material has a good degradation effect on bisphenol A, in order to further verify its catalytic degradation efficiency, the catalytic degradation effect of the barium titanate / manganese dioxide composite material prepared in Example 1 and Comparative Example 1 on environmental pollutants similar to bisphenol A, such as halogenated hydrocarbons, aromatic hydrocarbons and their derivatives, was verified. The results are shown in Table 1.
[0037] Table 1: Degradation efficiency of composite materials for different pollutants
[0038]
[0039] The barium titanate / manganese dioxide composite material prepared in Example 1 has excellent degradation effects on bisphenol A, toluene, benzene and chloroform, and the degradation rates are all above 90%. However, the barium titanate / manganese dioxide composite material prepared in Comparative Example 1 has poor degradation effects on the above pollutants, and there are also obvious differences in the degradation efficiency for different pollutants.
[0040] Example 2
[0041] A method for preparing a composite catalyst is carried out according to the following steps:
[0042] (1) Add barium titanate to anhydrous ethanol and ultrasonicate for 1 min to obtain a suspension. The suspension is coated on a quartz glass sheet and placed in the reaction chamber of an atomic layer reaction device. The chamber is evacuated to 1×10 -5 Pa vacuum state, the amount ratio of barium titanate and anhydrous ethanol in the suspension is 1g:4mL;
[0043] (2) N2 was used as a carrier gas to bring the manganese source di(cyclopentadienyl)manganese into the reaction chamber with a carrier gas flow rate of 8 sccm. The reaction deposition was carried out under the conditions of a reaction chamber temperature of 250°C and a volume ratio of O3 and H2 / Ar of 9:1. In one reaction cycle (one deposition cycle), the manganese source pulse was 2 s, the N2 purge was 10 s, the O3 reaction pulse was 2 s, the H2 and Ar mixed gas pulse was 1 s, and the nitrogen purge was 15 s. The cyclic reaction deposition was repeated for 50 cycles (60 deposition cycles) to obtain a core-shell structured barium titanate / manganese dioxide composite material with a volume ratio of suspension to di(cyclopentadienyl)manganese of 1:2.
[0044] The degradation rates of the barium titanate / manganese dioxide composite material prepared in this embodiment for bisphenol A, toluene, benzene and chloroform are all above 90%.
[0045] Example 3
[0046] A method for preparing a composite catalyst is carried out according to the following steps:
[0047] (1) Add barium titanate to anhydrous ethanol and ultrasonicate for 1 min to obtain a suspension. The suspension is coated on a quartz glass sheet and placed in the reaction chamber of an atomic layer reaction device. The chamber is evacuated to 1×10 -5 Pa vacuum state, the amount ratio of barium titanate and anhydrous ethanol in the suspension is 1g:6mL;
[0048] (2) N2 was used as a carrier gas to bring the manganese source di(cyclopentadienyl)manganese into the reaction chamber with a carrier gas flow rate of 6 sccm. The reaction deposition was carried out under the conditions of a reaction chamber temperature of 280°C and a volume ratio of O3 and H2 / Ar of 9.5:0.5. In one reaction cycle, the manganese source pulse was 2 s, the N2 purge was 10 s, the O3 reaction pulse was 2 s, the H2 and Ar mixed gas pulse was 1 s, and the nitrogen purge was 15 s. The cyclic reaction deposition was repeated for 80 cycles (80 depositions) to obtain a core-shell structured barium titanate-manganese dioxide composite material with a volume ratio of suspension to di(cyclopentadienyl)manganese of 1:2.
[0049] The degradation rates of the barium titanate / manganese dioxide composite material prepared in this embodiment for bisphenol A, toluene, benzene and chloroform are all above 90%.
Claims
1. A method for preparing a composite catalyst, characterized in that: The steps include: (1) Add barium titanate to anhydrous ethanol and ultrasonicate for 1 min to obtain a suspension. The suspension is coated on a quartz glass sheet and placed in the reaction chamber of an atomic layer reaction device. The chamber is evacuated to 1×10 -5 Pa vacuum state, the amount ratio of barium titanate and anhydrous ethanol in the suspension is 1g:4~6mL; (2) The manganese source di(cyclopentadienyl)manganese was brought into the reaction chamber by N2, and the reaction deposition was carried out in an O3 atmosphere at a reaction chamber temperature of 250-280°C. Then, a mixed gas of H2 and Ar was introduced for treatment. The volume ratio of H2 to Ar was 9:1-9.5:0.
5. In one reaction cycle, the manganese source pulse was 2 s, the N2 purge was 10 s, the O3 reaction pulse was 2 s, the mixed gas pulse of H2 and Ar was 1 s, and the nitrogen purge was 15 s. The cyclic reaction deposition was performed for 50-80 cycles to obtain a core-shell structured barium titanate-manganese dioxide composite material. The volume ratio of the suspension to di(cyclopentadienyl)manganese was 1:
2.
2. Use of the composite catalyst prepared by the method of claim 1 in the degradation of organic matter in wastewater.
3. The use according to claim 2, characterized in that: The composite catalyst is used for the degradation of bisphenol A, toluene, benzene and chloroform in waste water.
Citation Information
Patent Citations
Composite piezoelectric catalytic material and preparation method and sludge dewatering application thereof
CN111068659A
Ammonia synthesis catalyst and process for its preparation
WO2023217782A1